2012
DOI: 10.1093/nar/gks568
|View full text |Cite
|
Sign up to set email alerts
|

Reconstitution of translation from Thermus thermophilus reveals a minimal set of components sufficient for protein synthesis at high temperatures and functional conservation of modern and ancient translation components

Abstract: Thermus thermophilus is a thermophilic model organism distantly related to the mesophilic model organism E. coli . We reconstituted protein translation of Thermus thermophilus in vitro from purified ribosomes, transfer ribonucleic acids (tRNAs) and 33 recombinant proteins. This reconstituted system was fully functional, capable of translating natural messenger RNA (mRNA) into active full-length proteins at temperatures up to 65°C and with yields up to 60… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
54
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
1
1

Relationship

4
6

Authors

Journals

citations
Cited by 53 publications
(55 citation statements)
references
References 80 publications
1
54
0
Order By: Relevance
“…1). Furthermore, the ancient EF-Tu protein exhibits the closest phenotypic property to the endogenous EF-Tu in terms of observed melting temperature (Tm) and its activity in a reconstructed in vitro translation machinery in which all other components necessary for translation besides EF-Tu are provided from the contemporary translation machinery (Gaucher et al 2008; Zhou et al 2012). This suggests that co-evolution between EF-Tu and aa-tRNAs/ribosome/nucleotide-exchange-factors in E. coli since the divergence of the ancestral and modern EF-Tu forms has not prevented the ancestral EF-Tu from interacting with the modern E. coli translation components (Kacar and Gaucher 2012).…”
Section: Introductionmentioning
confidence: 99%
“…1). Furthermore, the ancient EF-Tu protein exhibits the closest phenotypic property to the endogenous EF-Tu in terms of observed melting temperature (Tm) and its activity in a reconstructed in vitro translation machinery in which all other components necessary for translation besides EF-Tu are provided from the contemporary translation machinery (Gaucher et al 2008; Zhou et al 2012). This suggests that co-evolution between EF-Tu and aa-tRNAs/ribosome/nucleotide-exchange-factors in E. coli since the divergence of the ancestral and modern EF-Tu forms has not prevented the ancestral EF-Tu from interacting with the modern E. coli translation components (Kacar and Gaucher 2012).…”
Section: Introductionmentioning
confidence: 99%
“…1). Furthermore, the ancient EF-Tu protein exhibits the closest phenotypic property to the endogenous EF-Tu in terms of observed melting temperature (Tm) and its activity in a reconstructed in vitro translation machinery in which all other components necessary for translation besides EF-Tu are provided from the contemporary translation machinery (Gaucher et al 2008;Zhou et al 2012). This suggests that co-evolution between EF-Tu and aa-tRNAs/ribosome/nucleotide-exchange-factors in E. coli since the divergence of the ancestral and modern EF-Tu forms has not prevented the ancestral EF-Tu from interacting with the modern E. coli translation components (Kacar and Gaucher 2012).…”
Section: Electronic Supplementary Materialsmentioning
confidence: 99%
“…Then, they observed that the thermophilic ancestor adapted to cooler environment progressively as the temperature of the ancient ocean decreased (Gaucher et al 2008 ). In addition, the reconstructed elongation factor Tu works correctly in an extant thermophilic organisms (Zhou et al 2012 ). Similarly, Hart et al ( 2014 ) investigated how modern mesophilic and thermophilic ribonuclease H1 (RNH) have adapted to low and high temperatures, respectively.…”
Section: Other Studies To Synthesize Ancestral Proteinsmentioning
confidence: 99%